Analisis Determinan Tingkat Kemiskinan Se-Eks Karesidenan Surakarta Di Jawa Tengah Tahun 2005-2014 - Adiratnakusuma, Bayu, Dr. Daryono Soebagyo.,MEc (2017)
This research aimed to analyze the effect of unemployment, Gross Regional Domestic Product (GDP) , population and inflation throughout the year 1999 - 2013 in Surakarta Residency. The analysis technique used in this study is a panel data regression. It used to determine the factors that affect the level of poverty in Surakarta Residency along 2005 - 2014. The data used is data panel to take the 7 regencies / cities contained in Surakarta Karisidenan with a time series of ten years (2005 -2014). The results showed that the Fixed Effects Model (FEM) is a panel data regression model is most appropriate. Under the influence of the validity of the test (t test) at significance (α) of 0.05 unemployment, population and inflation significant positive effect on the level of poverty, while the GDP discount a significant negative effect on poverty levels in Surakarta years 2005-2014.